Control and Monitor of IoT Devices using EOG and Voice Commands - Ayman WAZWAZ; Mohammad ZIADA; Lubna AWAWDEH; Mutaz TAHBOUB (International Journal of Applied Methods in Electronics and Computers, 2020)
This paper aims to deploy a machine to control and monitor home devices, and to assist people who suffer from spinal cord injuries to control devices, such injuries cause people to lose their ability to use their body movements, normal people may use voice commands as well. The prototype used electrooculography (EOG) system [1, 2, 3]. The patients who suffer from spinal cord injuries may use this system to control household appliances and use the voice system to control home devices. This prototype use internet of things (IoT) technology through Wi-Fi and Arduino microcontroller to capture eye muscle movement signals, that are taken from patients, or voice signals to compare them with pre-recorded voice commands. Many tests have been made to assure correctness and speed using different environment parameters and conditions. The error rate was 2.5% for EOG and 1% for voice commands in the best cases. The idea could be developed further, smartphones and mobile data can be used for controlling and monitoring homes remotely.